A taylor-like expansion of a commutator with a function of self-adjoint, pairwise commuting operators - Rasmussen, Morten Grud (MATHEMATICA SCANDINAVICA, 2012)
Let $A$ be a $ u$-vector of self-adjoint, pairwise commuting operators and $B$ a bounded operator of class $C^{n_0}(A)$. We prove a Taylor-like expansion of the commutator $[B,f(A)]$ for a large class of functions $f\colonR^ u→R$, generalising the one-dimensional result where $A$ is just a self-adjoint operator. This is done using almost analytic extensions and the higher-dimensional Helffer-Sjöstrand formula.